PREVALENSI KEJADIAN MASTITIS SUBKLINIS DAN HUBUNGANNYA DENGAN JUMLAH SEL SOMATIK PADA SAPI PERAH DI KOPERASI SUSU WARGA MULYA - , ARIEF RAHMADI; , drh. Heru Susetya, M.P., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mastitis is one of disease in dairy cows that cause a lot of loss to the breeders, especially decrease in milk production, decreased milk quality, milk disposal, cost of care and treatment, early culling cattle and new purchase of dairy cows. The occurrence of mastitis is always associated with three factors which are cattle, agent of infection and environment. This aims of this research was determining the prevalence and risk factors related to the incidence of mastitis and somatic cell counts in dairy cows in Warga Mulya Dairy Cooperative. A total of 80 cows from 30 farmers were taken as the study sample. Samples were taken from the farm in Warga Mulya Dairy Cooperative is divided in the 4 District. District of Pakem, Turi, Ngemplak and Tempel. Samples were examined directly on the paddle using reagent California Mastitis Test (CMT) and test of IPB-1 , then the samples which reacted positively to the reagents were used for somatic cells count by the method of Breed. Field data obtained from the questionnaires were filled based on interviews with farmers and direct observation of stall conditions and livestocks. The data obtained were analyzed using chisquare test, odds ratio and kappa for measuring reagent spesific between California Mastitis Test (CMT) and IPB-1. The results showed 43 cows reacted positively with CMT and IPB-1 reagent (prevalence 53,75%). A total of 42 cows also have amount of somatic cell were over the amount that was required in Indonesia and 1 cows with somatic cell counts were below the amount specified standards. Factors cow age, reproductive status, stall, stall conditions, drainage and preparation before milking were associated on the incidence of mastitis. Kappa test results obtained values of 0.64 which indicating good agreement between the reactants CMT and IPB-1 on subclinical mastitis test.